2020
DOI: 10.37934/cfdl.12.11.6171
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat Transfer Characteristic of Inclined Oval Trench Dimples With Numerical Simulation

Abstract: In this work, flow and heat transfer in a channel having oval trench dimples were investigated numerically. 3-D channel flow with a cross-section of 300-mm width and 32-mm height were created using Computational Fluid Dynamic (CFD) with ANSYS, Fluent (V.15.0). Five oval trench dimples with 3-mm depth, 10.0-mm width and 45-mm length arranging with a single row and in-line configuration were located on the bottom surface of the channel. Reynolds number based on hydraulic diameter of the channel were fixed at Re=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The symbols λ and λ t are molecular thermal diffusivity and turbulent thermal diffusivity, respectively. Adding turbulators in the fluid flow duct enhances heat transfer, as predicted by calculating Nusselt numbers [26,27]. In addition to this enhancement, the friction factor also increases.…”
Section: Governing Equationsmentioning
confidence: 88%
“…The symbols λ and λ t are molecular thermal diffusivity and turbulent thermal diffusivity, respectively. Adding turbulators in the fluid flow duct enhances heat transfer, as predicted by calculating Nusselt numbers [26,27]. In addition to this enhancement, the friction factor also increases.…”
Section: Governing Equationsmentioning
confidence: 88%
“…Piya et al, [8] carried out numerical simulation in order to study heat transfer characteristic of inclined oval trench and found that area of high Nusselt number corresponded to the area of high total pressure coefficient. When inclined angle became larger, the areas of Nusselt number and high total pressure coefficient took place at dimple edge in +Z direction.…”
Section: Introductionmentioning
confidence: 99%